Critical developments of 2018: A review of the literature from selected topics in transfusion. A committee report from the AABB's Clinical Transfusion Medicine Committee. Issue 8 (30th May 2019) - Cohn, Claudia S.; Allen, Elizabeth S.; Cushing, Melissa M.; Dunbar, Nancy M.; Friedman, David F.; Goel, Ruchika; Harm, Sarak K.; Heddle, Nancy; Hopkins, Courtney K.; Klapper, Ellen; Perumbeti, Ajay; Ramsey, Glenn; et al.
Abstract : BACKGROUND: The AABB compiles an annual synopsis of the published literature covering important developments in the field of transfusion medicine. An abridged version of this work is being made available in TRANSFUSION, with the full‐length report available as Appendix S1 (available as supporting information in the online version of this paper). STUDY DESIGN AND METHODS: Papers published in late 2017 and 2018 are included, as well as earlier papers cited for background. Although this synopsis is comprehensive, it is not exhaustive, and some papers may have been excluded or missed. RESULTS: The following topics are covered: "big data" and "omics" studies, emerging infections and testing, platelet transfusion and pathogen reduction, transfusion therapy and coagulation, transfusion approach to hemorrhagic shock and mass casualties, therapeutic apheresis, and chimeric antigen receptor T‐cell therapy. CONCLUSION: This synopsis may be a useful educational tool.